Is there a relationship between gluten sensitivity and postural tachycardia syndrome?. Issue 12 (December 2016) - Penny, Hugo A.; Aziz, Imran; Ferrar, Melloney; Atkinson, Jayne; Hoggard, Nigel; Hadjivassiliou, Marios; West, John N.; Sanders, David S.
Abstract : Background: We have noticed that patients with postural tachycardia syndrome (PoTS) were placing themselves on a gluten-free diet without medical consultation. Therefore, we aimed to evaluate the prevalence of coeliac disease and self-reported gluten sensitivity in a cohort of patients with PoTS and compare this with local population data. Methods: A total of 100 patients with PoTS were recruited to complete a questionnaire that screened for gluten sensitivity, related symptoms and dietary habits. Patients were also assessed for coeliac disease. For comparison, the local coeliac prevalence was determined from a total of 1200 controls (group 1) and a further 400 controls (group 2), frequency matched for age and sex, who completed the same questionnaire. Results: Overall, 4/100 (4%) patients with PoTS had serology and biopsy-proven coeliac disease. This was significantly higher than the local population prevalence of coeliac disease (12/1200, 1%; odds ratio: 4.1, 95% confidence interval: 1.3–13.0; P =0.03). PoTS patients also had a higher prevalence of self-reported gluten sensitivity (42 vs. 19%, respectively; odds ratio: 3.1, 95% confidence interval: 2.0–5.0; P <0.0001) compared with age-matched and sex-matched controls. Conclusion: This is the first study to suggest a potential association between gluten-related disorders and PoTS. A prospective study evaluating this relationship further may enable a better understanding and management of these conditions.